2010
DOI: 10.1111/j.1740-0929.2009.00696.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of intramuscular connective tissue in meat texture

Abstract: The structure, composition and amount of intramuscular connective tissue (IMCT) vary tremendously between muscles, species and breeds, and certainly contribute to meat texture. With animal growth, collagen crosslinks become more stable, and the structural integrity of IMCT increases. These changes increase the mechanical properties of IMCT, contributing to the toughening of meat. Intramuscular fat deposits, mainly in the perimysium between muscle fiber bundles, result in marbling. This causes the remodeling of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
107
3
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(123 citation statements)
references
References 76 publications
2
107
3
11
Order By: Relevance
“…Muscle characteristics are influenced by management factors such 24 as breed, age, sex and diet (Cuvelier et al 2006;Jurie et al 2006). They depend on the 25 contractile and metabolic properties of the different categories of the myofibres (type I, type 26 IIa, type IIx and/or type IIb) that compose the bovine skeletal muscles 2009) and on the attachment of these fibres to the intramuscular connective tissues (IMCT) of 28 which collagen is the major protein component (Nishimura 2010;Dubost et al 2013). Muscle 29 fibre composition is known to influence colour, tenderness and ultimate pH (Muchenje et al 30 2009; Wu et al 2014;Gagaoua et al 2015a) and intramuscular fat (IMF) content is believed to 31 influence tenderness and juiciness (Mandell et al 1997;Scollan et al 2001;Gagaoua et al 32 2014).…”
mentioning
confidence: 99%
“…Muscle characteristics are influenced by management factors such 24 as breed, age, sex and diet (Cuvelier et al 2006;Jurie et al 2006). They depend on the 25 contractile and metabolic properties of the different categories of the myofibres (type I, type 26 IIa, type IIx and/or type IIb) that compose the bovine skeletal muscles 2009) and on the attachment of these fibres to the intramuscular connective tissues (IMCT) of 28 which collagen is the major protein component (Nishimura 2010;Dubost et al 2013). Muscle 29 fibre composition is known to influence colour, tenderness and ultimate pH (Muchenje et al 30 2009; Wu et al 2014;Gagaoua et al 2015a) and intramuscular fat (IMF) content is believed to 31 influence tenderness and juiciness (Mandell et al 1997;Scollan et al 2001;Gagaoua et al 32 2014).…”
mentioning
confidence: 99%
“…Sasaki et al (2006) indicated that the differences in the DSC curve between tissue-level and extracted fat from pork may be caused by a component other than the fat-soluble fraction in adipose tissues, such as water, ECM molecules, and other water-soluble substances. Nishimura (2010) pointed out that the development of adipose tissues in marbled meat would disrupt the structure of the IAT and remodel the ECM. Judging from this idea, it is supposed that the thermal properties of IAT would be altered by collagenase treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, other studies focusing on fibrosis in DMD have asserted that fibrosis not only exacerbates disease progression, but may also prevent the success of many targeted gene therapies [20,35,36]. Further, the mechanical properties of fibrosis are likely altered throughout the course of disease, as its stiffness has been correlated with both the amount of collagen and the number of cross-links [5,37,38]. Together, these results emphasize the complexity of fibrosis, and the need to better understand its development in DMD.…”
Section: Discussionmentioning
confidence: 99%